Networked aspects of lifelong work-integrated learning: The BUFFL case - Lindqvist, Marcia Håkansson; Olofsson, Anders D.; Mozelius, Peter (Proceedings of the International Conference on Networked Learning, 2024)
The increasingly digitalised and continuously changing working life needs a continuous lifelong professional development that preferably is networked and work-integrated. This this study builds upon university teachers' and course participants’ experiences from a technology enhanced project called BUFFL A pilot project that combines truly work-integrated learning with lifelong learning, in a strive to address the contemporary need for continuous professional development. The important aim in the BUFFL project is to develop a model for collaborative, flexible, and lifelong professional development. A new and interesting concept in the BUFFL project was to involve concept of Bringing Your Own Data for activities in course modules. The aim of this study is to describe and discuss the lifelong work-integrated learning in the BUFFL project from a networked learning perspective. Data were gathered from e-mail interviews with teachers, e-mail conversations between teachers, facilitators and course participants, and from course evaluations. Results from the data sources have been grouped into three main themes in an inductive thematic analysis. Findings show that in academia, in industry, and in the in between a potential is found in the form of collaborative learning. A networked collaboration that should involve the theories from academia, combined with real-world-problems in the workplace, to achieve a fruitful meeting between academia and the industry